Pengaruh Lingkungan Kerja Non Fisik dan Coaching terhadap Kinerja Karyawan PT Graha Layar Prima CGV Grand Indonesia Jakarta Pusat - Alfi Muhammad Dzikri; Anah Furyanah (MAMEN: Jurnal Manajemen, 2026)
This study aims to examine the influence of non-physical work environment and coaching on employee performance at PT. Graha Layar Prima (CGV) Grand Indonesia, Central Jakarta. The focus of this research is based on the importance of non-physical work environment aspects such as interpersonal relationships, communication, emotional support, social skills, and organizational culture, as well as coaching factors including change, concern, learning, and relationship, which are assumed to improve employee performance. The research method used is quantitative with a descriptive-analytic approach. Primary data were collected through questionnaires distributed to 70 respondents, while data analysis was conducted using multiple linear regression with the assistance of SPSS. The results indicate that the non-physical work environment has a positive and significant effect on employee performance, as does coaching, which also positively and significantly affects employee performance. Simultaneously, the non-physical work environment and coaching have a significant effect on employee performance. This is evidenced by the F-test value of 77.365, which is greater than the F-table value of 3.1337, with a coefficient of determination (R²) of 0.698. This means that 69.8% of the variation in employee performance can be explained by both variables, while the remaining 30.2% is influenced by other factors outside the scope of this study. Thus, creating a conducive non-physical work environment and implementing effective coaching are proven to enhance employee performance at PT. Graha Layar Prima.